Respuesta :

Answer:

see explanation

Step-by-step explanation:

A

when 2 equal bases are being multiplied together their exponents are added together, that is

[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex]

B

[tex]12^{5x}[/tex] × [tex]12^{-7}[/tex] = [tex]12^{5x-7}[/tex]

C

[tex]x^{4}[/tex][tex]y^{6k+2}[/tex] × x²[tex]y^{-1}[/tex]

= [tex]x^{4}[/tex] × x² × [tex]y^{6k+2}[/tex] × [tex]y^{-1}[/tex]

= [tex]x^{(4+2)}[/tex] × [tex]y^{(6k+2-1)}[/tex]

= [tex]x^{6}[/tex][tex]y^{6k+1}[/tex]

#A

  • a^b+a^c=a^b+c

#B

  • 12^5x×12^-7
  • 12^5x-7

#C

  • x⁴y^6k+2×x²y^-1
  • x⁶y^6k+2-1
  • x⁶y^6k+1
ACCESS MORE